2016
DOI: 10.1105/tpc.15.00900
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathway for Triacylglycerol Biosynthesis Is Responsible for the Accumulation of Massive Quantities of Glycerolipids in the Surface Wax of Bayberry (Myrica pensylvanica) Fruit

Abstract: ORCID ID: 0000-0003-4019-0681 (J.P.S.)Bayberry (Myrica pensylvanica) fruits synthesize an extremely thick and unusual layer of crystalline surface wax that accumulates to 32% of fruit dry weight, the highest reported surface lipid accumulation in plants. The composition is also striking, consisting of completely saturated triacylglycerol, diacylglycerol, and monoacylglycerol with palmitate and myristate acyl chains. To gain insight into the unique properties of Bayberry wax synthesis, we examined the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 74 publications
1
28
0
Order By: Relevance
“…De novo synthesis of monoacylglycerol (MAG) in plant cells has been previously described [12,13] and was shown to be catalyzed by GPAT4 and GPAT6 enzymes, which use αω-dicarboxylic and ω-hydroxy acyl-CoA as acyl-donors for production of sn2-MAG [12,14]. The MAGs have been considered initially as precursors for synthesis of waxy polymers; however, their conversion to DAGs has been reported in Nicotiana bethamina leaves [14] and recently in fruits of Myrica pensylvanica [15].…”
Section: Tag Synthesis Pathways In Algaementioning
confidence: 99%
“…De novo synthesis of monoacylglycerol (MAG) in plant cells has been previously described [12,13] and was shown to be catalyzed by GPAT4 and GPAT6 enzymes, which use αω-dicarboxylic and ω-hydroxy acyl-CoA as acyl-donors for production of sn2-MAG [12,14]. The MAGs have been considered initially as precursors for synthesis of waxy polymers; however, their conversion to DAGs has been reported in Nicotiana bethamina leaves [14] and recently in fruits of Myrica pensylvanica [15].…”
Section: Tag Synthesis Pathways In Algaementioning
confidence: 99%
“…Article pathway of cutin triacylglycerols. 53 The authority role of a similar acyltransferase may indicate a similar function in stored apples.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Bayberry ( Myrica pensylvanica ) fruits synthesize an extremely thick and unusual layer of crystalline surface wax that accumulates up to 32% of dry fruit weight, the highest reported surface lipid accumulation in plants (Simpson and Ohlrogge, 2016 ). Recently, it was strikingly found that the surface wax is primarily composed of glycerolipids, notably triacylglycerol and diacylglycerol with saturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%